2014
DOI: 10.1016/j.euroneuro.2014.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of variation in the BDNF gene on social stress sensitivity and the buffering impact of positive emotions: Replication and extension of a gene–environment interaction

Abstract: A previous study reported that social stress sensitivity is moderated by the brain-derived-neurotrophic-factor(Val66Met) (BDNF rs6265) genotype. Additionally, positive emotions partially neutralize this moderating effect. The current study aimed to: (i) replicate in a new independent sample of subjects with residual depressive symptoms the moderating effect of BDNF(Val66Met) genotype on social stress sensitivity, (ii) replicate the neutralizing impact of positive emotions, (iii) extend these analyses to other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 46 publications
2
23
0
Order By: Relevance
“…Because of the role of the vMPFC in cognitive and affective processes (Montag et al 2008; Mühlberger et al 2014; van Winkel et al 2014) as well as in BDNF-dependent extinction learning in preclinical and human studies (Chhatwal et al 2006; Soliman et al 2010; Milad & Quirk 2012; Park & Poo 2013), we performed post-hoc ROI analyses on this region in order to assess effects of interest across the various experimental questions addressed here. A bilateral vMPFC ROI based on Milad & Quirk’s 2012 vMPFC human analog of the infralimbic cortex was drawn using the anatomical ROI toolbox, ITK SNAP (see insert in Fig.…”
Section: Methods and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the role of the vMPFC in cognitive and affective processes (Montag et al 2008; Mühlberger et al 2014; van Winkel et al 2014) as well as in BDNF-dependent extinction learning in preclinical and human studies (Chhatwal et al 2006; Soliman et al 2010; Milad & Quirk 2012; Park & Poo 2013), we performed post-hoc ROI analyses on this region in order to assess effects of interest across the various experimental questions addressed here. A bilateral vMPFC ROI based on Milad & Quirk’s 2012 vMPFC human analog of the infralimbic cortex was drawn using the anatomical ROI toolbox, ITK SNAP (see insert in Fig.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…In line with these findings, in both transgenic mice and healthy humans, impairments in fear extinction learning and altered amygdala-vMPFC function has been demonstrated in BDNF Met carriers, relative to BDNF Val homozygotes (Soliman et al 2010). Additionally, the BDNF Val 66 Met polymorphism is involved in neural responses to visual observation of positive and negative emotional stimuli in humans (Montag et al 2008; van Winkel et al 2014). However, the role of this genotype in the neural mediation of socially relevant higher-order aversive and reward-related learning is not well defined in humans, despite the fact that such learning is proximate to the maintenance of well-being by means of the adaptive capacity to flexibly adapt to both threatening and favorable contexts in our modern, socially-complex environment.…”
Section: Introductionmentioning
confidence: 99%
“…Further, in favour of a pre-morbid vulnerability, there is emerging evidence that increased NA-reactivity to social stress is indicative of a genetic predisposition to respond with more NA to small social stressors and may function as an intermediate endophenotype of MDD [43,42,29,27]. More specifically, specific variations of the BDNF gene, Met carriers of the BDNF Val66Met genotype, are associated with a higher NAreactivity to social stress [43,42]. This is in line with evidence that sensitivity to perceived social stress is an important vulnerability factor in teenagers that develop depression at a later stage [39].…”
Section: Social Stressmentioning
confidence: 99%
“…BDNF level has been linked to healthy lifestyle factors (Chan et al, 2008). In addition, serum BDNF levels and environmental pressure are also closely related (Chen et al, 2013;van Winkel et al, 2014). Our results showed that BDNF promoter methylation in the Xinjiang Han elderly is significantly higher than in the Ningbo Han elderly.…”
Section: Discussionmentioning
confidence: 49%